Music Intervention in Learning for Better Emotional Stimulation of Early Childhood Children in Islamic Schools - Sameto, Mayang Belia; Nalus, Syafrul; Jingga Sameto, Putri Merak; Suci Nadiati, Rahma; Sameto, Puti Rinai Bening (El-Rusyd, 2024)
This research aims to analyze how emotional changes in early childhood children after musical treatment and intervention. The author uses the 4D Research and Development method as a research approach to create music products as learning media. The music products produced in this research have been validated and assessed by four experts, related to the fields of educational technology, psychology, language and music. These expert assessments are carried out repeatedly to produce quality products. The product results were then tested in a learning process involving thirty students as research subjects.  All data was analyzed using SPSS 21 software with correlation analysis techniques. The results of the analysis regarding the use of the resulting music products have run well in accordance with the design that has been determined. Furthermore, the results of statistical analysis show that music intervention is proven to stimulate children's emotions in early childhood in the learning process with a value of 0.041. These results show that music intervention in the learning process can be used as an alternative for teachers to stimulate students' emotions, besides that it is necessary to carry out other studies related to this context by future researchers.